Modifications of some rabbit spermatic parameters in relationship to high ambient temperatures - Finzi A.; Morera P.; Macchioni P. (Rabbit production in hot climates, 1994)
To evaluate volume and concentration of semen in hot environmental conditions, ten NZW rabbit bucks, selected for homogeneous sperm output (ml 0.6 + or - 0.1) with artificial vagina, were located into a climatic chamber. Semen collection, by two consecutive ejaculations, was performed three times a week. Mean pre-trial ambient temperature was 20.3 degrees Celsius + or - 1.1 and relative humidity was 69.1 per cent + or - 3.5. The animals were then exposed for two months to a mean ambient temperature of 29.8 degrees Celsius + or - 0.6 and relative humidity of 67.9 per cent + or - 1.7 with a daily remission for three hours to ambient temperature of 24.7 degrees Celsius + or - 0.8, relative humidity 72.5 per cent + or - 6.0. Total volume had a mean value of ml 1.10 + or - 0.29 in the pre-stress period, and underwent a non significant increase to ml 1.23 + or - 0.28 from second to ninth week. No difference was observed in the pre-trial period and in the first week of treatment between first and second ejaculation of each semen collection. The difference appeared and became statistically significant starting from the second week (P less thyan 0.05). This difference was due to an increase of the volume in the first ejaculation (from ml 0.56 + or - 0.20 to ml 0.67 + or - 0.21 in the pre-trial period and in the hot period respectively, + 19.6 per cent, P less than 0.05) since the volume of second ejaculation showed non significant variations. The output of spermatozoa per ml (x 10 to the sixth) was 107.2 + or - 50.9 in the pre-stress period. It showed a quick increase (185.5 + or - 98.1, + 73.1 per cent, P less than 0.01) in the first weeks of stress then it stabilized itself at an intermediate value (156.2 + or - 91.5, + 45.7 per cent, P less than 0.05).
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)